Quantifying post-bleaching endolithic bioerosion on coral reefs in the Maldives - Prabowo, Herbian Hokky (Nanyang Technological University, 2025)
A reef carbonate budget is an important eco-geological assessment tool to measure net rates of gross carbonate production (bioconstruction) and removal (bioerosion) by organisms within a coral reef system. The resultant budget values serve as an indicator for reef ecological health and allows for near-future projections of reef growth potential and ecosystem services (e.g., habitat complexity, wave dissipation) to be quantified. While there are various methods for estimating carbonate production on reefs, there remains only few quantitative datasets of in situ endolithic erosion rates globally. Furthermore, previous studies have often utilized experimental blocks to estimate bioerosion rates over time, but these may not directly apply to the different coral morphologies (e.g., shapes, skeletal density, surface area) of coral populations on reefs. Better quantification of endolithic bioerosion is particularly critical following major ecological disturbance events, such as coral bleaching, where the post-mortem remains of corals provide significant amounts of new substrate for breakdown by boring taxa. In these post-bleaching reefs, the removal of calcium carbonate by endolithic borers, even in small amounts, weakens the reef structure and increases its fragility, contributing to the collapse of the reef structure and the flattening of reef ecosystems. This flattening has practical consequences: reef ecosystem services, such as acting as a habitat for fish biomass and wave protection, are all linked to how much structure or 3D complexity a reef has. Thus, the contribution of endolithic eroders to reef flattening can directly impact the rest of the reef system. Here, we develop a high-resolution method to analyze endolithic bioerosion rates for a range of coral morphotypes (branching, columnar, digitate) collected one year and eight months following a major bleaching event in the Maldives, within the central Indian Ocean. Bioholes of boring organisms were reconstructed from uCT (micro-CT) scans of 36 corals collected at lagoon and reef sites. Results show that boring taxa biodiversity, wave intensity and surface area to volume ratio (SAV) were not significant controls on the rates of bioerosion on reefs, but the morphology did show a significant effect on bioerosion rates. We also infer the presence of two species of endolithic worms within these Maldivian corals, defined by distinct separation in the volume distribution of the two species. Our results represent the first quantitative rates of endolithic boreholes from in situ coral samples of a post-bleaching reef, providing critical real-world evidence on the role of endolithic fauna in the removal of carbonate and subsequent breakdown of reef framework: an important process that must occur before reef recovery can begin.